2015
DOI: 10.3390/nu7063959
|View full text |Cite
|
Sign up to set email alerts
|

Apples and Cardiovascular Health—Is the Gut Microbiota a Core Consideration?

Abstract: There is now considerable scientific evidence that a diet rich in fruits and vegetables can improve human health and protect against chronic diseases. However, it is not clear whether different fruits and vegetables have distinct beneficial effects. Apples are among the most frequently consumed fruits and a rich source of polyphenols and fiber. A major proportion of the bioactive components in apples, including the high molecular weight polyphenols, escape absorption in the upper gastrointestinal tract and rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
100
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(105 citation statements)
references
References 221 publications
(354 reference statements)
1
100
0
4
Order By: Relevance
“…Chen et al., ). Prebiotic DF like pectin may improve gut barrier function and reduce intestinal permeability and uptake of lipopolysaccharide, a proinflammatory cytokine secretion promoter, through the modulation of gut microbiota (Koutsos, Tuohy, & Lovegrove, ). Oral administration of butyrate‐producing probiotic bacteria Butyricicoccus pullicaecorum decreased intestinal myeloperoxidase (MPO), tumor necrosis factor α (TNF‐α), and interleukin (IL)‐12 levels of colitis rats, alleviating the proinflammatory microenvironment (Eeckhaut et al., ).…”
Section: Effects Of Dfs From Fruits and Vegetables On Host Healthmentioning
confidence: 99%
“…Chen et al., ). Prebiotic DF like pectin may improve gut barrier function and reduce intestinal permeability and uptake of lipopolysaccharide, a proinflammatory cytokine secretion promoter, through the modulation of gut microbiota (Koutsos, Tuohy, & Lovegrove, ). Oral administration of butyrate‐producing probiotic bacteria Butyricicoccus pullicaecorum decreased intestinal myeloperoxidase (MPO), tumor necrosis factor α (TNF‐α), and interleukin (IL)‐12 levels of colitis rats, alleviating the proinflammatory microenvironment (Eeckhaut et al., ).…”
Section: Effects Of Dfs From Fruits and Vegetables On Host Healthmentioning
confidence: 99%
“…Apple ( Malus domestica ) is one of the most widely cultivated trees, whose fruits are a very popular foodstuff [1, 2]. The composition of phenolic compounds present in apple fruits and their antioxidative properties have been extensively investigated [35].…”
Section: Introductionmentioning
confidence: 99%
“…Several observational studies have shown that apple intake is associated with a reduced risk of cardiovascular disease and all-cause mortality (1) . Intervention studies in animals show that apples can significantly decrease total and LDL-cholesterol but this has been only shown in a few well-controlled human studies as detailed in our review (2) . Moreover, other markers such as vascular function and inflammation are less explored (3) .…”
mentioning
confidence: 76%